The Dynamic Regulatory Genome of Capsaspora and the Origin of Animal Multicellularity - Sebé-Pedrós, Arnau (Cell, 2016)
The unicellular ancestor of animals had a complex repertoire of genes linked to multicellular processes. This suggests that changes in the regulatory genome, rather than in gene innovation, were key to the origin of animals. Here, we carry out multiple functional genomic assays in Capsaspora owczarzaki, the unicellular relative of animals with the largest known gene repertoire for transcriptional regulation. We show that changing chromatin states, differential lincRNA expression, and dynamic cis-regulatory sites are associated with life cycle transitions in Capsaspora. Moreover, we demonstrate conservation of animal developmental transcription-factor networks and extensive network interconnection in this premetazoan organism. In contrast, however, Capsaspora lacks animal promoter types, and its regulatory sites are small, proximal, and lack signatures of animal enhancers. Overall, our results indicate that the emergence of animal multicellularity was linked to a major shift in genome cis-regulatory complexity, most notably the appearance of distal enhancer regulation.